Investigation of Mechanical and Tribological Characteristics of Medical Grade Ti6al4v Titanium Alloy in Addition with Corrosion Study for Wire EDM Process - S. Prakash; C. S. Abdul Favas; I. Ameeth Basha; R. Venkatesh; M. Prabhahar; V. P. Durairaj; K. Gomathi; Haiter Lenin (Advances in Materials Science and Engineering)
Metals used in biomedical applications are frequently coated to prevent oxidation and metallic ion release, both of which can be harmful due to toxic effects. To prevent these adverse effects of metals, researchers have focused their efforts on developing various coating techniques, facilitating surface coating, or obtaining functional surfaces. (WEDM) is now considered a difficult method of obtaining functional surfaces for medical applications. The properties of the surface and subsurface layers obtained by the WEDM method are particularly interesting in this regard. The analysis utilised RSM-based computational technique to evaluate the WEDM characteristics (MRR SR) of Ti6Al4V Titanium Alloy in biomedical applications. The biggest drawback of the material in the biomedical industry, which includes orthopedic applications and dental implants, would be that it releases harmful atoms such as iron, chromium, and nickel into the bodily fluid environment. To combat the problems, a hydroxyapatite layer applied to the metal implant improves biocompatibility, osteocompatibility, and antimicrobial properties. By comparing the Modified Differential Evolution (MDE) approach to the basic differential evolution (DE) optimization strategy, the effectiveness of the MDE approach has been established. According to the cyclic polarized test, the Hap coated Titanium material had better corrosion resistance than the pure sample. The Hap coated titanium material has a higher zone of inhibition than the pure sample. The next step is to synthesis hydroxyapatite from cuttlebone, which is then electrodeposited onto titanium. FTIR, electrochemical tests, FESEM, and SEM were used to describe the coated sample, as well as an antibacterial test using E. Coli and B. Cereus bacteria. Because it is porous, the Hap coating helps bone tissue growth by preventing detrimental metal ions from escaping into the biological medium. The corrosion inhibition efficiency of the coated sample was performed in SBF (NaHCO3—0.35 g/L, MgCl2.6H2O—0.30 g/L, CaCl2·2H2O—0.37 g/L, K2HPO4. 3H2O—0.23 g/L, Na2SO4—0.071 g/L, NaCl—7.99 g/L, KCl—0.22 g/L, Tris’s buffer—6.063 g/L) solution using the potentiodynamic polarisation method and the solution pH was maintained.